A Study of Distributed Computing and Performance Analysis Using Cloud and Grid Computing - Meenakshi Sundaram, P (International Journal of Computer Sciences and Engineering, 2025)
To build the productivity of any undertaking, we require a framework that would give high performance along adaptabilities and cost efficiencies for client. Distributed computing, as we are all mindful, has turned out to be extremely prevalent over the previous decade. Distributed computing has three noteworthy sorts, in particular, cluster, grid and cloud. Keeping in mind the end goal to build up a high performance distributed framework, we have to use all the previously mentioned three sorts of computing. In this manuscript, we should first have a presentation of all the three sorts of distributed computing. In this manner analyzing them we should investigate inclines in computing and green supportable computing to upgrade the performance of a distributed framework. At last introducing the future degree, we close the manuscript proposing a way to accomplish a Green high performance distributed framework utilizing cluster, grid and cloud computing.